Obtenção de parâmetros construtivos para antenas de microfita utilizando o Método Taguchi de otimização - Lira, Ruann Víctor de Andrade (Brasil, 2017)
The applications of microstrip antennas cover a large area of Telecommunications, especially in systems that require components of volume and reduced weight, such as aerospace communications. Hence numerous researchers have been studying, more and more, techniques of optimization in the design of these antennas. Thus, this work has as main objective the optimization of microstrip antenna design. For this, the Taguchi Method is used in which each physical parameter is defined from the frequency of operation desired by the user, of the electric characteristics of the dielectric that will be used to make the antenna (substrate thickness and dielectric constant of the material) and definition of optimization limits (maximum and minimum values) that physical parameters can achieve. Specifically, the analysis uses the Taguchi method with boundary treatment so that the optimum final value does not fall outside the specified range. In the analysis, rectangular and circular patches are considered for projects in the frequency bands specific to WLAN. In the paper, numerical and experimental results are presented for loss of return. Comparisons are made between these results. A good agreement between the results is observed. Suggestions for continuity of work are also presented.
Keywords: MétodoTaguchi; Otimização; Antenas de microfita; CNPQ::ENGENHARIAS::ENGENHARIA ELETRICA E DE COMPUTAÇÃO